Taking punishment into your own hands: An experiment on the motivation underlying punishment - Peter Duersch; Julia Müller (University of Heidelberg, Department of Economics, 2010)
In a punishment experiment, we separate the demand for punishment in general from a possible demand to conduct punishment personally. Subjects experience an unfair split of their earnings from a real effort task and have to decide on the punishment of the person who determines the distribution. First, it is established whether the allocator's payoff is reduced and, afterwards, subjects take part in a second price auction for the right to (physically) carry out the act of payoff reduction. This auction only resolves who will punish, not whether punishment takes place, so only subjects with a demand for personal punishment should bid.
urn:nbn:de:bsz:16-opus-106694
Keywords: D03; C92; 330; personal punishment; real effort task; experiment; auction; desire to win; Auktionstheorie; Soziale Beziehungen; Test